Simultaneous determination of 74 pesticide residues in Panax notoginseng by QuEChERS coupled with gas chromatography tandem mass spectrometry - Huijun Li; Jieshan Wu; Chao Chen; Wenfeng Xin; Wensheng Zhang (Food Science and Human Wellness, 2021)
This study established a method for the simultaneous determination of 74 pesticide residues in Panax notoginseng by QuEChERS pretreatment method coupled with GC-MS/MS, and carried out pesticide residue analysis on 20 batches of market samples in China. The samples were extracted with acetonitrile, cleaned up with primary secondary amine (PSA) and octadecylsilane (C18) and determined by GC-MS/MS in multiple reaction monitoring (MRM) mode. Matrix-matched calibration was recommended to combat the matrix effect. A good linearity was observed in the range of 10 − 500 ng/mL with correlation coefficients ≥ 0.9950. The mean recoveries for most of the pesticides were in the range of 70% − 120% with RSD < 20%. The limits of detection ranged 0.28–2.00 μg/kg, while the limits of quantification were 0.94–6.65 μg/kg. Following the application of “top-down” approach, the expanded measurement uncertainty for all the analytes was <30%. The proposed method was successfully applied to determine pesticide residues in 20 market samples in China, where 9 pesticides were detected and quintozene exceeded the criteria domestically and abroad.